European tourism impact and management - Davis, Grant; Classroom Video ([New Jersey] : Classroom Video : Insight Media [distributor], 1998)
This video examines the history and growth of tourism in Europe, the impact of tourism on the physical and human environment, how authorities manage tourism and the future strategies for tourism
Title from title screen
Executive producer, John Davis, Jo Adendorffcamera and editing, Grant Davis ; graphics, Roddy Balle
Keywords: Tourism -- Europe; Tourism -- Europe -- History; Tourism -- Europe -- Marketing